News on intellectual property in the global digital environment - Díaz-Noci, Javier (Anuario ThinkEPI, 2013)
Review of trends in copyright and author rights. The Web has helped to highlight the differences between the Anglo-Saxon (common law) and Latin (civil law) worlds, and at the same time has spurred movement worldwide toward more homogeneous policies between countries. The progress is described.